Buffalo Bill Cody, A Man of the West - Ingraham, Prentiss, 1843-1904 (Book collections on Project MUSE., 2019)
Transcription of a biography of Buffalo Bill Cody, by Prentiss Ingraham, which was serialized in the Duluth Press from July 13, 1895 through May 16, 1896. The biography was divided into three parts: "Man of the West" (Cody's childhood years), "Led by Destiny" (his Army career), and "Honors Easy" (Cody's theatrical career and scouting for the Army).